Strategi Komunikasi Pemasaran MAD For Makeup dalam Menciptakan Brand Image Sebagai Merek Kosmetik untuk Gen Z - Muthiah, Farras (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research discusses the marketing communication strategies implemented by MAD For Makeup in an effort to create a brand image as a major player in the cosmetics industry, especially in attracting attention and building engagement with the Generation Z target market. The research method involves a comprehensive analysis of the marketing communication campaigns carried out by MAD For Makeup, with a focus on the use of social media, celebrity endorsements, and product innovation. This research aims to evaluate the extent to which this communication strategy has succeeded in creating a strong and relevant brand image for Generation Z consumers. The findings of this research are expected to provide in-depth insight regarding the impact of marketing communication strategies on brand perception among Generation Z, as well as provide guidance for the cosmetics industry in understanding dynamic market preferences and expectations.